SYSTEM CHANGES IN A GROWING SOUTH AFRICAN ORGANISATION - von Fintel, Carmen Monica (My University, 2011)
This research study examines how changes in management structure and the concomitant technology changes in a growing organisation impact on each other, and to investigate the intended and unintended influence these elements have on the manner in which work is done. A social constructivist approach is taken to this researching using an ethnography of a case currently undergoing technology changes. Orlikowski’s (1992) structurational model of technology is used to frame the research. The research reveals that the planning and implementation of a system change are absolutely fundamental to its success. The research further shows that a system change in isolation cannot bring about the requisite changes an organisation may require. The research suggests that systems be planned as a part of a greater change process, and that the change be well communicated to all stakeholders with the requirements planning and implementation to be undertaken thoroughly.
MBA - WBS
Keywords: Change management; System changes